A case study of design imagination in product design. (1st January 2013) - Chen, Kuen-Meau
This research was conducted through a literature review, case studies, and interviews with experts on award-winning works in international design competitions. Through qualitative analysis of these design projects, the author identified several paths leading from imaginative constructs to conceptual development in the design process: thematic relationships, conjunctive interpretation, the transfer of attributes, inherited attributes, causal relationships, analogical relationships, multi-level inclusive relationships, and the interpretation of contrasting meaning. Lastly, statistical analysis was used to determine the weight of each conceptual development mode in the design process. Results show that the most significant mode of conceptual development in the overall design process is causal relationships, followed in decreasing order by multi-level inclusive relationships, the interpretation of contrasting meaning, and lastly, the interpretation failure. It is hoped that the results of this study will serve as a useful reference in design education, particularly with regard to the development of imaginative and creative capacity.